+0  
 
0
52
2
avatar

GIven the system of equations, 

xy= 6 - 2x - 3y
yz= 6 - 4y - 2z
xz= 156 - 4x - 3z

find the positive solution for x

 Dec 6, 2020
 #1
avatar+428 
+1

It should just use substitution to get x=9

 Dec 6, 2020
 #2
avatar+114221 
+1

xy  =  6  - 2x   - 3y

yz  =  6  - 4y   - 2z

xz =  156  - 4x   - 3z

 

xy + 3y  =  6 - 2x                     xz + 3z  = 156  - 4x

y ( x + 3)  = 5 -2x                    z( x + 3)  =  156 - 4x

y =      (6-2x) / ( x + 3)             z   =  (156 - 4x)  / ( x + 3)

 

(6-2x)(156 - 4x)  / (x + 3)^2   =  6  - 4 ( 6-2x)/(x + 3)  -2 (156 - 4x)/(x + 3)    simplify

 

(6 -2x) (156 - 4x)  =  6( x + 3)^2  - 4(6 - 2x)(x + 3)  - 2(156- 4x)(x + 3)

 

8x^2 -336x +936  =  6x^2 + 36x + 54  + 8x^2   -72 + 8x^2 -288x -936

 

14x^2  +  84x   -1890  =  0 

 

7x^2  + 42x   -  945  =   0

 

x^2  +  6x  - 135  =   0   

 

(x -9) ( x + 15)   =  0

 

x  = 9   is the positive  solution   for x

 

 

cool cool cool

 Dec 6, 2020

23 Online Users

avatar